Sistem Informasi Manajemen Pegawai Research & Learning in Faculty of Education - Kaehe, Agita (Jurnal Ilmiah Wahana Pendidikan, 2025)
Employee Management Information System (SIMP) is a technological solution designed to manage various aspects of human resource management in an organization. This system aims to increase the efficiency and effectiveness of employee data management, including the recruitment process, performance appraisal, training and development, as well as compensation and benefits management. SIMP provides features that enable integrated and automatic management of personnel, attendance, leave and payroll data. With the support of web-based technology, SIMP enables fast, accurate and secure data access, and supports better decision making by providing comprehensive reports and analysis. This system is also equipped with strict security mechanisms to protect the confidentiality and integrity of employee data. The implementation of SIMP is expected to help organizations optimize human resource management, reduce administrative burden, and increase overall productivity